Development and characterisation of biodegradable electrospun polyhydroxybutyrate (PHB) / rice husk derived bioactive glass ceramic (RHBGC) composite scaffolds / Shyrose Wahid - Shyrose, Wahid (2017)
Bioglass derived from rice husk ash (RHBGC) is considered to be natural bioactive glass. It is known for its remarkable properties that exhibits biocompatibility, biodegradable, bioactivity and excellent mechanical properties. Nanofibrous structure is one of the key factors that is considered in scaffold fabrication because it can resemble natural extra cellular matrix (ECM). Electrospinning technique enables the production of nanofibrous scaffold at low cost. RHBGC can be obtained by multistep preparation which involves silica extraction from rice husk and sol gel synthesis of bioglass. The RHBGC of various amount (0.2, 0.4 and 0.6g) is blended with Polyhydroxybutyrate (PHB) to strengthen the mechanical property of the scaffold. The scaffold is fabricated with electrospinning technique. The scaffolds were characterized using Field Emission Scanning Electron Microscope (FESEM), Fourier Transform Infrared Spectroscopy (FTIR) and contact angle. The FESEM results demonstrate that RHBGC in PHB produced nanofibrous electrospun scaffold with high porosity and interconnected fibers. However, increase in concentration of RHBGC can cause agglomeration which can lead to bead formation and reduce porosity. The formation of chemical bond between the bioactive glass and polymer were studied through FTIR. Water contact angle results shows variations in the angle due to different concentrations of RHBGC in the polymer. The results demonstrates PHB/RHBGC composite scaffold to be promising material for Bone Tissue Engineering (BTE).